Soft palatal wound associated with dental avulsion: an exceptional consequence of a bovine horn blow in children - Zegbeh-N'guessan Eric Kouassi; Koné Rokiatou; Djémi Ernest Martial; Bérété Pornan Issa Jules; Irié Gohi bi Serge; Crézoit Gréberet Emmanuel (EDP Sciences, 2020)
Introduction: Palatal wounds in children as a result of a bovine horn blow have rarely been observed in adults and almost never in children. They are serious and can lead to fatal complications. Dental injuries by bovine horn are also rare. Observation: This study presents the unpublished case of an 11-year-old child who developed a soft palate penetrating wound associated with traumatic loss of the lower incisors as a result of a bovine horn blow. The surgical outcomes were positive. Comment: This type of childly bovine trauma is common in rural African agricultural areas. Dental trauma probably served as a mitigator to the soft palate trauma thus avoiding an associated injury of the hard palate and a contusion of the internal carotid artery. Although, there is a consensus among practitioners on leaving palate wounds to heal spontaneously, we chose a debridement and a suture because of the severity of the wound and the potential risk of turning into an oral-nasal fistula. Conclusion: The potential severity of palate and dental damage from bovine horns should lead to dehorning of cattle for better protection of children in rural agriculture.